Kratek pogled na Pedičkove "Poglede na telesno vzgojo, šport in rekreacijo" - Hosta, Milan (Šport (Ljubljana), 2013)
When I read Pediček's work I regretted I had not delved into his title work before I wrote my doctoral dissertation. Perhaps I would not have written it very differently but I would undoubtedly have given additional weight to some arguments. His book is a comprehensive interdisciplinary theoretical work, the first of its kind in the then Yugoslavia, which still makes for topical reading due to its basic philosophical-pedagogical nature. Not only did Dr Pediček very systematically structure the study of physical education, recreation and sport but, in a visionary way, he also substantiated the problems that are topical today through a broad conceptualisation and sensibility for the biopolitical and pedagogical value of sport. Today, the readings of Pediček acquire additional value as the Marxist thought that pervaded our social environment at the time has again become relevant in all fields of social engagement, including a consideration of the role of sport in modern society.
Keywords: anthropology; antropologija; pedagogika; pedagogy; Pediček, Franc, 1922-2008; physical culture; physical education; recreation; rekreacija; scientific method; scientific research; sport; sport education; šport; športna vzgoja; telesna kultura; telesna vzgoja; znanstveno raziskovanje